ANALISIS PERILAKU PERCAYA DIRI PESERTA DIDIK KELAS XI MADRASAH ALIYAH ISLAMIYAH PONTIANAK - Kurniati Kurniati; H. M. Asrori; Luhur Wicaksono (Universitas Tanjungpura, 2021)
AbstractThis research discusses the students’ self-confidence of Class XI MA Islamiyah Pontianak for the 2020/2021 academic year. The problems in this research discusses self-confidence, optimistic and objective behavior, sense of responsibility, rational and realistic thinking. This research aims to identify and describe self-confidence, optimistic and objective behavior, sense of responsibility, rational and realistic thinking. This research is a survey research with a descriptive method through a quantitative approach. The research’s subject is the students of class XI with a population of 42 students. The technique of date collection in this research is self-confidence inventory and the tools used in this research are indirect communication. Based on the results of data analysis, the self-confidence of students in class XI MA Islamiyah Pontianak was 88%, which means they were in the